2013
DOI: 10.1038/ajg.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Medications and the Risk of Hepatocellular Cancer: A Systematic Review and Meta-Analysis

Abstract: Several preclinical and observational studies have shown that anti-diabetic medications (ADMs) can modify the risk of hepatocellular cancer (HCC) in patients with diabetes mellitus (DM). We performed a systematic review and meta-analyses of studies evaluating the effect of metformin, thiazolidinediones (TZDs), sulfonylureas, and/or insulin on the risk of HCC. We conducted a systematic search of Medline, EMBASE, and Web of Science up to August 2012. Studies were included if they (1) evaluated and clearly define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
214
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(240 citation statements)
references
References 48 publications
18
214
3
5
Order By: Relevance
“…A second meta-analysis by the same authors found that metformin use might also be associated with a 50% relative risk reduction in hepatocellular cancer, while sulfonylurea use may be associated with a 62% increase in the relative risk (Singh, et al, 2013c). Lastly, the group found that metformin, thiazolidinediones, and insulin use had no significant effect on pancreatic cancer risk, while sulfonylurea use was associated with a 70% increase in the odds of pancreatic cancer (Singh, et al, 2013b).…”
Section: Metforminmentioning
confidence: 92%
“…A second meta-analysis by the same authors found that metformin use might also be associated with a 50% relative risk reduction in hepatocellular cancer, while sulfonylurea use may be associated with a 62% increase in the relative risk (Singh, et al, 2013c). Lastly, the group found that metformin, thiazolidinediones, and insulin use had no significant effect on pancreatic cancer risk, while sulfonylurea use was associated with a 70% increase in the odds of pancreatic cancer (Singh, et al, 2013b).…”
Section: Metforminmentioning
confidence: 92%
“…The use of insulin and sulfonylurea was associated with a 161% and 62% increased risk of HCC respectively, while the use of metformin was associated with 50% reduction in the incidence of HCC incidence [23]. While it is commonly postulated that insulin and insulin secretagogues have direct effects of carcinogenesis, it may also be possible that the risk of HCC development is due in part to the insulin/ insulin secretagogues stimulated progression of liver tissue to advanced fibrosis or cirrhosis, especially since HCC typically develops following the sequence of chronic hepatic inflammation to fibrosis and cirrhosis [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Metoprolol has been associated with an inhibition of low-density lipoprotein cholesterol synthesis in a study on human cell lines, thereby reducing the risk of HCC (11). Metformin has been associated with a decreased risk of HCC in a meta-analysis of 8 observational studies (odds ratio=0.50), whereas insulin usage increased the risk on HCC (odds ratio=1.62) (12). Metformin decreases insulin resistance and inhibits the mammalian target of rapamycin pathway, thereby inhibiting cell proliferation and inducing apoptosis (13).…”
Section: Discussionmentioning
confidence: 99%